Oncolytic vaccinia virus delivering tethered IL-12 enhances antitumor effects with improved safety - David L Bartlett; Yan Ge; Zong Sheng Guo; Enyong Dai; Weilin Liu; Zuqiang Liu; Haiyan Wang; Jinghua Ren; Lingjuan Chen; Hongqi Chen; Junjie Ye; Congrong Ma; et al. (Journal for ImmunoTherapy of Cancer)
Immune checkpoint blockade is arguably the most effective current cancer therapy approach; however, its efficacy is limited to patients with “hot” tumors, warranting an effective approach to transform “cold” tumors. Oncolytic viruses (especially properly armed ones) have positive effects on almost every aspect of the cancer–immunity cycle and can change the cancer–immune set point of a tumor. Here, we tested whether oncolytic vaccinia virus delivering tethered interleukin 12 (IL-12) could turn a “cold” tumor into a “hot” tumor while avoiding IL-12’s systemic toxicity. Our data demonstrated that tethered IL-12 could be maintained in the tumor without treatment-induced toxic side effects. Moreover, the treatment facilitated tumor infiltration of more activated CD4+ and CD8+ T cells and less Tregs, granulocytic myeloid-derivedsuppressor cells, and exhausted CD8+ T cells, with increased interferon γ and decreased transforming growth factor β, cyclooxygenase-2, and vascular endothelial growth factor expression, leading to transformed, immunogenic tumors and improved survival. Combined with programmed cell death 1 blockade, vaccinia virus expressing tethered IL-12 cured all mice with late-stage colon cancer, suggesting immediate translatability to the clinic.